Nutrition Intervention Process for Heart Failure Patients according to Their Nutritional Problems - Lee, Hosun (Clin Nutr Res, 2021)
Patients with heart failure (HF) need nutritional management such as sodium restriction and healthy eating habits to relieve symptoms and to manage chronic disease. This case study examined 3 patients who had different nutritional problems and responded positively to the nutrition management program. Patient 1 and 2 had high levels of energy intake and were obese. Patient 1 had a habit of irregular binge eating and frequently consumed sweetened snacks and fast foods. He was advised to eat regular 3 meals per day with balanced food choices. He decreased his energy consumption to the recommenced intake and his body mass index had dropped to 22.9 kg/m(2) by his second follow-up visit. Patients 2 ate 3 meals regularly but ate a large amount of food. Although he decreased his energy intake to 97% of the recommended intake, he should be advised to increase his protein intake at the 1st follow-up session because he decreased his protein intake less than 90% of the recommended amount. Patient 3 reduced food intake by half due to dyspnea caused by HF before hospitalization, but symptoms improved after discharge and his energy as well as sodium intake increased. In the second follow-up, his nutritional diagnosis was excessive sodium intake and nutritional intervention was performed to reduce sodium intake. This study showed that additional nutritional problems might arise throughout the nutritional intervention process. Therefore, follow-up nutritional counseling should be held to evaluate the compliance with the nutrition management guidelines and to decide whether additional nutrition problems are suggested.